Characterisation of Some Copper(ll), Nickel(ll) and Cobalt(ll) Coordination Compounds with N-2-Carbomethoxyphenyl-N1-phenylthiourea. - RAI, H.C.; KUMAR, RAMESH; SHARMA, K.K.; RAI, B.K. (Asian Journal of Chemistry, 2010)
A number of coordination compounds of the types, M(HL)2, M(H2L)2X2 and M(HL)2Y2 where M = Co(II), Ni(II) or Cu(II), H2L= N-2-carbomethoxyphenyl-N1-phenylthiourea, X = Cl– or Br– and Y = ammonia or pyridine have been synthesised and characterised on the basis of elemental analyses, magnetic susceptibility, infrared and electronic spectral data.